Comparison between static and semi-dynamic models for microcosm biofilm formation on dentin - Daiana Moreli Soares dos Santos; Juliana Gonçalves Pires; Aline Silva Braga; Priscila Maria Aranda Salomão; Ana Carolina Magalhães (University of São Paulo, 2019)
Abstract Microcosm biofilm has been applied to induce carious lesions in dentin. However, no study has been done to compare the impact of the type of model for providing nutrients to microcosm biofilm formation on dentin. Objective This study compared the performance of two kinds of models (static and semi-dynamic) on the biofilm formation and the development of dentin carious lesions. Material and Methods In both models, biofilm was produced using inoculum from pooled human saliva mixed with McBain saliva for the first 8 h (5% CO2 and 37°C). Afterwards, for the static model, the samples were placed in 24-wells microplate containing McBain saliva with 0.2% sucrose, which was replaced at 24 h. In the semi-dynamic model, the samples were submitted to artificial mouth system with continuous flow of McBain saliva with 0.2% sucrose (0.15 ml/min, 37°C) for 10 h a day (for the other 14 h, no flow was applied, similarly to the static model). After 5 days, biofilm viability was measured by fluorescence and dentin demineralization by transverse microradiography. Results Biofilm viability was significantly lower for the static compared with semi-dynamic model, while dentin demineralization was significantly higher for the first one (p<0.05). The static model was able to produce a higher number of typical subsurface lesions compared with the semi-dynamic model (p<0.05). Conclusions The type of model (static and semi-dynamic) applied in the microcosm biofilm may have influence on it's viability and the severity/profile of dentin carious lesions.